2018
DOI: 10.4103/0366-6999.229888
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rapid Eye Movement Sleep Behavior Disorder on Obstructive Sleep Apnea Severity and Cognition of Parkinson's Disease Patients

Abstract: Background:Rapid eye movement (REM) sleep behavior disorder (RBD) and obstructive sleep apnea (OSA) are the most common sleep disorders in Parkinson's disease (PD). The aim of this study was to identify whether RBD could alleviate OSA severity in PD patients and its effect on cognitive impairment.Methods:From February 2014 to May 2017, we recruited 174 PD patients from the Second Affiliated Hospital of Soochow University, all of whom underwent polysomnography (PSG). We collected clinical data, PSG results, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
3
32
0
Order By: Relevance
“…Surprisingly, the authors found that patients with abnormal persistence of chin muscle tone still presented obstructive apnoea during REM sleep, and similar findings were described by HUANG et al [46]. It may be reasonable that there is a correlation between motor disability and apnoea, as suggested in some studies [42,44], but the role of PD medications is not clear, and it has to be specified that in these studies, motor disability and apnoea were assessed in the "on" state, so the real contribution of dopaminergic drugs could not be clearly assessed.…”
Section: Apnoea In Parkinson's Diseasesupporting
confidence: 81%
“…Surprisingly, the authors found that patients with abnormal persistence of chin muscle tone still presented obstructive apnoea during REM sleep, and similar findings were described by HUANG et al [46]. It may be reasonable that there is a correlation between motor disability and apnoea, as suggested in some studies [42,44], but the role of PD medications is not clear, and it has to be specified that in these studies, motor disability and apnoea were assessed in the "on" state, so the real contribution of dopaminergic drugs could not be clearly assessed.…”
Section: Apnoea In Parkinson's Diseasesupporting
confidence: 81%
“…This is supported by one study showing that 63% of patients with PD and RBD had mild cognitive impairment (MCI) as opposed to 33% with isolated PD and 33% with idiopathic RBD [183]. Furthermore, studies suggest that RBD and OSA together can act synergistically to increase cognitive dysfunction in PD [37,175]. Interestingly, our group found that OSA treatment with CPAP improved RBD symptoms in a cohort of mostly early stage PD patients [185].…”
Section: Impact Of Rem Behavior Disorder On Pd Manifestations and Osamentioning
confidence: 67%
“…However, evidence is discordant. One study found that patients with the combination of PD, OSA, and RBD had a higher nadir oxygen saturation throughout the whole night and during REM sleep [37]. This is supported by other studies which have also observed a lower apnea-hypopnea index in patients with RBD [174,175].…”
Section: Impact Of Rem Behavior Disorder On Pd Manifestations and Osamentioning
confidence: 68%
See 2 more Smart Citations